Kepemimpinan Kepala Madrasah Aliyah Nurul Bahri dalam Meningkatkan Minat Calon Siswa di Kabila Bone Kabupaten Bone Bolango - Panue, Abdul Ishak; Rachman, Ellys; Thalib, Tety (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
This study aims to obtain an overview of how the Leadership of the Principal of Madrasah Aliyah Nurul Bahri in Increasing the Interest of Prospective Students in Kabila Bone, Bone Bolango Regency. This study used a qualitative approach. Data collection techniques are carried out by means of observation and interviews with several informants and documentation related to the research problem. Based on the results, it can be concluded that the Principal had quite good communication skills, especially in terms of accepting new students. He actively communicates with teachers, staffs, and parents of students. However, some teachers and students considered the communication to be less open in other matters and tends to be authoritarian. It is able to motivate teachers and students by highlighting achievements and other positive activities such as olympiads, tahfiz, OSIS, and scouts. They feel motivated, although some informants consider the motivation given is not evenly distributed and not always consistent. In general, the motivational ability is quite good, but needs to be improved and to be more comprehensive. Supervisory ability The principal is directly involved in the new student admission program and routinely monitors and evaluates the progress. They felt the supervision, but there is another perspective that shows that he is too strict and does not provide enough space for discussion. This means, that supervision has been effective but needs to be accompanied by transparant. It should be more open in communicating also in internal matters. Motivation needs to be given evenly and continuously.